2015
DOI: 10.15171/mejdd.2016.08
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pneumatic Balloon Dilation in Patients with Symptomatic Relapse after Failed Heller Myotomy: A Single Center Experience

Abstract: BACKGROUND Although Heller myotomy is one of the most effective treatments for achalasia, it may be associated with early or late symptom relapse in some patients. Therefore, additional treatment is required to achieve better control of symptoms. Aim: To evaluate the safety and efficacy of pneumatic balloon dilation (PBD) in patients with symptom relapse after Heller myotomy. METHODS Thirty six post-myotomy patients were evaluated from 1993 to 2013. Six patients were excluded from the analysis because of como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
(16 reference statements)
0
12
0
2
Order By: Relevance
“…Recently, Amani et al . reported a 70% response rate for patients with recurrent symptoms post‐HM . However, previous studies have found more variable and dismal efficacy rates ranging from 9% (1 of 11 patients) to 23% (5 of 22 patients) .…”
Section: Discussionmentioning
confidence: 93%
“…Recently, Amani et al . reported a 70% response rate for patients with recurrent symptoms post‐HM . However, previous studies have found more variable and dismal efficacy rates ranging from 9% (1 of 11 patients) to 23% (5 of 22 patients) .…”
Section: Discussionmentioning
confidence: 93%
“…Of the 87 patients treated with PD,[ 8 9 10 11 ] only the cause of failure was defined in one study. Of 113 patients in this study, the presence of an incomplete myotomy combined with fibrosis was identified in seven patients as the cause of myotomy failure, and in one patient, the origin of the failure was incomplete myotomy without fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…When no gross anatomic abnormalities are present, PD or POEM can be considered. Both procedures show equally modest efficacy rates, but PD is often regarded a less invasive first step 71–79 . In the event of recurrence due to a too tight or twisted fundoplication, or a more complex anatomy with oesophageal distortion, fibrosis or a post‐myotomy diverticulum, redo surgery may be considered.…”
Section: Achalasia Treatmentmentioning
confidence: 99%